THE PREDICTORS OF RE-BLEEDING IN CHRONIC LIVER DISEASE PATIENTS AFTER ENDOSCOPIC VARICEAL - Khan, Tahir Ullah; Khurram Saleem,; Faisal Amin Baig,; Atif Masood,; Arsalan Nawaz,; Wali Khan, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Variceal bleeding is a key and most fatal complication observed in chronic liver disease patients with portal hypertension and is a major contributor to the high morbidity and mortality seen in these patients. Exploring the predictors of rebleeding in chronic liver disease patients is of paramount importance to alter disease course and impact on morbidity and mortality. Methods: About 50 patients with chronic liver disease who previously had evidence of varices on upper GI endoscopy and had at least one episode of rebleeding after EVBL were included in this study. Patients were assessed for the possible contributors to rebleeding through complete history, clinical examination, coagulation profile and platelet count, ultrasound features (splenic size and portal pressure), and upper GI endoscopic findings (site and grade of varices, red sign). Sample selection was done using non-probability purposive sampling technique and sample size calculated using the standard WHO formula. Data was entered and analyzed using SPSS version 20. Results: In this study, mean age of the patients was 51.34±6.34 years with male predominance (64%). Rebleeding was significantly associated with grade of varices, presence of red sign on upper GI endoscopy, site of varices, splenic size and coagulopathy. Conclusion: Rebleeding in chronic liver disease patients following EVBL is predicted by grade, extent and site of varices, red sign on upper GI endoscopy, splenic size and coagulation disturbances.